Lebanon : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2017)
This Selected Issues paper analyzes the impact of the Syrian crisis on Lebanon's economy. Output growth in Lebanon has fallen sharply since the onset of the Syrian crisis and is too low to accommodate new job seekers, or to address the needs of Lebanon's more vulnerable population. Moreover, low growth is taking a toll on public debt dynamics, raising the prospect of higher borrowing costs and constrained social and investment spending-both are much needed to improve the quality of public spending and direct it toward more useful and productive uses. The authorities have presented an ambitious proposal to the international community, which centers on a multiyear effort to stimulate growth and employment through a targeted series of investment initiatives.